Food supply chain management - Bourlakis, Michael A.;Weightman, Paul W H (Oxford, United Kingdom : Blackwell Publishers, 2004)
Food Supply Chain Management Edited by Michael A. Bourlakis and Paul W.H. Weightman. The food supply chain is a series of links and inter-dependencies, from farms to food consumers' plates, embracing a wide range of disciplines. Food Supply Chain Management brings together the most important of these disciplines and aims to provide an understanding of the chain, to support those who manage parts of the chain and to enhance the development of research activities in the discipline. Food Supply Chain Management follows a 'farm to fork' structure. Each chapter starts with aims and an introduction.
1 Introduction to the UK Food Supply Chain -- 2 The Food Consumer and the Supply Chain -- 3 Perceived Risk and Product Safety in the Food Supply Chain -- 4 Procurement in the Food and Drink Industry in the early 21st Century -- 5 The UK Livestock System -- 6 UK Crop Production -- 7 Food Manufacturing -- 8 Food Retailing, Wholesaling and Catering -- 9 Partnerships and Alliances in UK Supermarket Supply Networks -- 10 New Product Development and Information Technology in Food Supply Chain Management: The Case of Tesco -- 11 Third Party Logistics in the Food Supply Chain -- 12 Temperature Controlled Supply Chains -- 13 Factors Influencing Supply and Demand for Organic Foods -- 14 The US Food Supply Chain -- 15 The Future of Food Supply Chain Management.
Includes bibliographical references and index.
Keywords: FARM PRODUCE -- GREAT BRITAIN -- MARKETING